Efficient consensus algorithm for the accurate faulty node tracking with faster convergence rate in a distributed sensor network - Hossain, Rajkin; Khan, Muhidul Islam (© 2016 Springer Netherlands, 2016)
This article was published in the Eurasip Journal on Wireless Communications and Networking [©2016 Published by Springer International Publishing.] and the definite version is available at: http://dx.doi.org/10.1186/s13638-016-0698-x . The article website is at:http://jwcn.eurasipjournals.springeropen.com/articles/10.1186/s13638-016-0698-x